TUBERKULOSIS SEBAGAI ANCAMAN KESEJAHTERAAN SOSIAL DI KOMUNITAS PERTAMBANGAN EMAS SKALA KECIL - Nadya Kharima; Amelia Oktaviany; Lutfia Nuraeni; Bintang Andriansyah (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2026)
Tuberculosis is a serious infectious disease that is still a threat in Indonesia, especially in small-scale gold mining communities. Poor working conditions, low access to health services, social stigma, and economic pressure exacerbate transmission and have a significant impact on the social, economic, and psychological well-being of mining communities. This research aims to understand how Tuberculosis (TBC) is a threat to the social welfare of people in small-scale gold mining communities, especially in Pasirgombong Village, Bayah District, Lebak Regency. Through a descriptive qualitative approach and purposive sampling techniques, as well as data collection through in-depth interviews and documentation studies with several informants, results were found showing that the spread of TB disease in mining communities was influenced by closed, dusty, damp work environments and minimal air ventilation. These unhealthy working conditions are exacerbated by low awareness among the community, limited access to health or medical facilities, and the habit of not continuing treatment. Social stigma against TB sufferers also deepens social marginalization. The conclusion of this research is that it confirms that Tuberculosis (TB) is a multidimensional problem that not only threatens physical health, but also the social welfare of mining communities. Handling it requires increasing public awareness of health, equal distribution of health services, and social support between communities.